2009
DOI: 10.1105/tpc.108.065425
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Regulation ofLAX PANICLE1Protein Accumulation in Axillary Meristem Formation in Rice

Abstract: Axillary meristem (AM) formation is an important determinant of plant architecture. In rice (Oryza sativa), LAX PANICLE1 (LAX1) function is required for the generation of AM throughout the plant's lifespan. Here, we show a close relationship between AM initiation and leaf development; specifically, the plastochron 4 (P4) stage of leaf development is crucial for the proliferation of meristematic cells. Coincident with this, LAX1 expression starts in the axils of leaves at P4 stage. LAX1 mRNA accumulates in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
189
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(196 citation statements)
references
References 54 publications
1
189
2
4
Order By: Relevance
“…Genetic studies have revealed that initiation of the axillary meristem is regulated by genes such as MONOCULM1 (MOC1), LAX PANICLE1 (LAX1), and LAX2 in rice (Oryza sativa) (Komatsu et al, 2003;Li et al, 2003;Oikawa and Kyozuka, 2009;Tabuchi et al, 2011); barren stalk1 in maize (Zea mays) (Gallavotti et al, 2004); LATERAL SUPPRESSOR (LAS), REGULATOR OF AXILLARY MERISTEMS, and REGULATOR OF AXILLARY MER-ISTEM FORMATION (ROX) in Arabidopsis thaliana (Greb et al, 2003;Keller et al, 2006;Müller et al, 2006;Yang et al, 2012); and Lateral suppressor (Ls) and Blind in tomato (Solanum lycopersicum) (Schumacher et al, 1999;Schmitz et al, 2002). Most of these genes encode transcription factors belonging to the GRAS, MYB, and basic/helix-loop-helix families and are required for the early steps of axillary meristem initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have revealed that initiation of the axillary meristem is regulated by genes such as MONOCULM1 (MOC1), LAX PANICLE1 (LAX1), and LAX2 in rice (Oryza sativa) (Komatsu et al, 2003;Li et al, 2003;Oikawa and Kyozuka, 2009;Tabuchi et al, 2011); barren stalk1 in maize (Zea mays) (Gallavotti et al, 2004); LATERAL SUPPRESSOR (LAS), REGULATOR OF AXILLARY MERISTEMS, and REGULATOR OF AXILLARY MER-ISTEM FORMATION (ROX) in Arabidopsis thaliana (Greb et al, 2003;Keller et al, 2006;Müller et al, 2006;Yang et al, 2012); and Lateral suppressor (Ls) and Blind in tomato (Solanum lycopersicum) (Schumacher et al, 1999;Schmitz et al, 2002). Most of these genes encode transcription factors belonging to the GRAS, MYB, and basic/helix-loop-helix families and are required for the early steps of axillary meristem initiation.…”
Section: Introductionmentioning
confidence: 99%
“…During vegetative development in Arabidopsis, LAS and RAX1 influence the expression of ROX and axillary bud initiation occurs when ROX expression ceases . In contrast, LAX1 transcripts in rice are detected only after the axillary bud has initiated (Oikawa and Kyozuka 2009), suggesting that the molecular control of ROX-like genes may differ in timing between monocots and dicots. Initiation of axillary meristems takes place in the axils of bulb-scales (A) or leaves (B).…”
Section: Vegetative Propagationmentioning
confidence: 98%
“…The transcriptional up-and down-regulation, including differential accumulation of transcripts of these known/candidate genes in the AM/SAM tissues during vegetative and reproductive growth and their correlation with multiple auxin biosynthesis genes toward governing branch/panicle/tiller numbers have been well-understood in diverse crop plants, including legumes [13,[45][46][47][48][49][50][51][52][53][54][55][56]. The functional novel allelic variants from some of these selected genes like MAX2 and TB1 known to be involved in regulation of branch/panicle/tiller numbers, have been identified and functionally characterized by utilizing an integrated approach of candidate gene-based association analysis, fine mapping/mapbased cloning and differential transcript profiling in crop plants [16,[57][58][59].…”
Section: Tablementioning
confidence: 99%